Pengaruh Model Pembelajaran Project Based Learning terhadap Hasil Belajar Ilmu Pengetahuan Alam dan Sosial (IPAS) Siswa Kelas V Sekolah Dasar Negeri Saradan 1 Kecamatan Karangmalang Kabupaten Sragen - Pramesty Siwi, Tyas; Mulyati, Sri; Angganing, Paradika (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
The purpose of this study was to determine the effect of the project-based learning model on the learning outcomes of Science and Social (IPAS) fifth grade students of SD Negeri Saradan 1 Karangmalang District, Sragen Regency. The research method used quantitative research methods with an experimental approach with a Quasi Experimental design. The sample of this research was grade V students of SD Negeri Saradan 1 totaling 24 students. The results showed that the Project Based Learning learning model had an effect on the learning outcomes of fifth grade students of Saradan 1 State Elementary School. The basis for decision making from the pretest results of the control group obtained an average of 62.5 and the experimental group amounted to 64.17. While the posttest results of the control group obtained an average of 65.83 and the experimental group an average of 78.33. The t-test results show that the Sig. (2-tailed) 0.027 < 0.05 or t_hitung > t_tabel = 2.374 > 2.074 then Ho is rejected and Ha is accepted, meaning that there is an effect of the project-based learning model on the learning outcomes of IPAS class V students of Saradan 1 State Elementary School, Karangmalang District, Sragen Regency.